2012
DOI: 10.1016/j.eururo.2012.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Oncological Outcomes Following Surgical Management of Localised Renal Cancer

Abstract: Context: Renal cell carcinoma (RCC) accounts for 2-3% of adult malignancies. There remain uncertainties over the oncological outcomes for the surgical management of localised RCC. Objective: To systematically review relevant literature comparing oncological outcomes of surgical management of localised RCC (T1-2N0M0). Evidence Acquisition: Relevant databases including MEDLINE, Embase and the Cochrane Library were searched up to October 2010, and an updated scoping search was performed up to January 2012. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
0
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(207 citation statements)
references
References 56 publications
3
184
0
20
Order By: Relevance
“…9 Similarly, Yossepowitch and coworkers did not find any correlation between age and SM status at univariable (OR, 1; P ¼ .77) and multivariable (OR, 1; P ¼ .81) analysis. 11 Despite the previous, historical recommendations to remove at least 1 cm of normal-appearing renal parenchyma around the tumor to ensure negative margins, 25 the current indications for NSS have progressively changed: indeed, according to the recognized oncological safety of NSS even for T1b RCC, 3,26 and to the need for preservation of as much functioning healthy parenchyma as possible to minimize the loss of renal function, 27 NSS has moved from maximal parenchymal resection to minimal tissue removal. 20 In this scenario, several nonrandomized studies demonstrated the oncological safety of simple tumor enucleation compared with standard PN for the treatment of cT1 RCC, with a quite lower incidence of PSMs with respect to those observed after standard PN.…”
Section: Riccardo Schiavina Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…9 Similarly, Yossepowitch and coworkers did not find any correlation between age and SM status at univariable (OR, 1; P ¼ .77) and multivariable (OR, 1; P ¼ .81) analysis. 11 Despite the previous, historical recommendations to remove at least 1 cm of normal-appearing renal parenchyma around the tumor to ensure negative margins, 25 the current indications for NSS have progressively changed: indeed, according to the recognized oncological safety of NSS even for T1b RCC, 3,26 and to the need for preservation of as much functioning healthy parenchyma as possible to minimize the loss of renal function, 27 NSS has moved from maximal parenchymal resection to minimal tissue removal. 20 In this scenario, several nonrandomized studies demonstrated the oncological safety of simple tumor enucleation compared with standard PN for the treatment of cT1 RCC, with a quite lower incidence of PSMs with respect to those observed after standard PN.…”
Section: Riccardo Schiavina Et Almentioning
confidence: 99%
“…Nephron-sparing surgery (NSS) has become the standard of care for the conservative management of clinically localized renal cell carcinoma (RCC) whenever technically feasible, 1,2 offering equivalent oncological results, 3,4 and less renal function impairment 5,6 compared with radical nephrectomy. The excision of the tumor with a minimal margin of healthy parenchyma surrounding the neoplasm is currently considered the standard technique for partial nephrectomy (PN), to minimize the risk of PSMs and achieve optimal local cancer control.…”
Section: Introductionmentioning
confidence: 99%
“…According to oncological and quality-of-life outcomes, localised T1a-b tumours are best managed by partial nephrectomy (PN) rather than radical nephrectomy (RN), if technically feasible, irrespective of the surgical approach (LE 1b; [50,51]. On the basis of these data, laparoscopic RN has lower morbidity compared to open surgery (LE 1b).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Table 1) [7]. These reviews included all relevant published literature comparing surgical management of localised RCC (T1-2N0M0) [50,51], different strategies for small RMs, lymphadenectomy and adrenalectomy [6], caval venous thrombus, and local therapy of metastases from RCC. Owing to the very limited number of RCTs, nonrandomised studies (NRSs), prospective observational studies with controls, retrospective matched-pair studies, and comparative studies from the databases of well-defined registries were also included.…”
Section: Other Renal Tumoursmentioning
confidence: 99%
“…Bu kitleler genellikle iyi huylu bir yapıya sahip olmalarına karşın özellikle uzun yaşam beklentisi olan hastalarda bu kitlelerin gözlenmesi hem hasta, hem de cerrah için çok tercih edilen bir yöntem değildir (5). Böbrek hücreli kanser tedavisinde radikal nefrektomi altın standart olmasına karşın, klinik olarak T1 evresindeki (<7 cm) böbrek kanserlerinin tedavisinde nefron koruyucu cerrahi yaklaşımlar (açık, laparoskopik veya robot yardımlı parsiyel nefrektomi) üroloji pratiğinde yeni standart tedavi yöntemleri olarak yerini almıştır (6). Nefron koruyucu cerrahilerin onkolojik sonuçlarının gerçekten mükemmel olduğu gösterildikten sonra özellikle cerrahi açıdan riskli ve ciddi komorbiditeleri olan hasta grubunda daha az invaziv ve komplikasyon oranları daha düşük olan ablatif yöntemlerin uygulanması gündeme gelmiştir.…”
unclassified